Managing penicillin resistant pneumococcal meningitis: an international id-iri study. - Erdem H,; Dogan E,; Ankarali H,; Dragovac G,; Seyman D,; Tarakci A, .; Dalmanoglu E,; Kaya-Kalem A,; Batirel A,; Senbayrak S,; Cvetanovska, M; Kazancioglu S,; et al. (Springer Science and Business Media LLC, 2025)
Penicillin-resistant pneumococcal meningitis (PRPM) is a challenging and fatal infection. We conducted a multicentre international retrospective study to evaluate the clinical features, outcomes, predictors of outcomes antimicrobial efficacy and drug susceptibility in patients with PRPM. The study, conducted through the "Infectious Diseases-International Research Initiative" across 33 centers in 11 countries, analyzed PRPM patients treated between 2019 and 2024 using univariate and multivariate analyses. A total of 138 patients were included. Of these, 83 (60.1%) were fully cured, 27 (19.6%) died, and 28 (20.3%) survived with sequelae. Mortality was associated with ICU admission (OR 14.886; p = 0.021), mechanical ventilation (OR 7.205; p = 0.049), and vasopressor use (OR 8.983; p = 0.025). Higher CSF leukocyte count (OR 0.854; p = 0.060) and blood leukocyte count (OR 0.283; p = 0.021) were linked to lower mortality risk. Patients who developed sequelae were more likely to require mechanical ventilation (OR 9.354; p = 0.001), experience recurrent meningitis (OR 5.562; p = 0.081), and have lower platelet counts (OR 0.001; p = 0.050), compared to those who fully recovered. Sequelae patients had higher GCS scores (OR 1.365; p = 0.014), more corticosteroid use (OR 5.301; p = 0.061), and less vasopressor use (OR 0.205; p = 0.019) compared to those who died. The antibiotic susceptibility profiles of the isolates in our PRSP cohort were: Ceftriaxone (75/134, 55.9%), meropenem (26/44, 59%), moxifloxacin (47/48, 97.9%). PRPM is a fatal disease in which mortality and sequelae occurring in two-fifths of cases. Severe illness markers such as ICU admission, mechanical ventilation, and vasopressor use, along with recurrent meningitis are linked to worse outcomes. Thrombocytopenia, low leukocyte counts, and lower GCS scores are indicators of poor prognosis, while corticosteroid therapy appears protective in PRPM. Therapeutic optimization is challenged by rising resistance and pharmacokinetic limitations, though moxifloxacin shows the highest susceptibility; further research is warranted. Keywords: Meningitis; Penicillin; Pneumococci; Resistant; Streptococcus pneumoniae.
Keywords: Meningitis; Penicillin; Pneumococci; resistant bacteria; Streptococcus pneumoniae